The Use of Bimanese Vowel in English Speaking - Muhayyah, Muhayyah (JOLLT Journal of Languages and Language Teaching, 2018)
This research was aimed at finding how Bimanese vowels interfere Bimanese students in speaking English. The techniques of collecting data were observation and video. The data was collected during the research subject did the presentation in the class. The data analysis used qualitative descriptive. Based on the finding, itâ€™s found there were positive and negative transfers. In positive transfer the Bimanese vowels had similar sound in English so the students from Bima were easy to pronounce the words for example, in vowel /a/ in a word argument, associate, after, discuss, /i/ in a word this, into, is, mean, /u/ in a word opportunity, role, argument, /e/ in a word recognize, based, object, /o/ in a word order, of, associate. In negative transfer because of Bimanese have a strong accent, stress and intonation so in some words like /a/, /i/, /u/, /e/ and /o/ when they speak some words in English they keep making a mistake for example the wordÂ â€œrecognizeâ€ (rÉ›kÉ”gnÉ‘Ä«z) was pronounce â€œrÉ›kÉ”gnÉ‘Ä«sÉ›dâ€ by a Bimanese student, the word â€œprocedureâ€ (prÓ™ÊƒÄ«dÉ›r) was pronounce â€œprÉ”ÊƒÉ›dÉ›rÊŠlâ€ by Bimanese student, the word â€œdifferentâ€ (dÄ«frÓ™nt) was pronounce â€œdifÉ›rÉ›nâ€ by Bimanese student, and the word â€œfamilyâ€ (fÓ•mÓ™lÄ«) was pronounce â€œfÉ›miliâ€ by Bimanese student. The Bimanese vowel could give interference to the Bimanese students during learning process because they still familiar with their language so in some words they keep make a mistake.